Edible plants from traditional Chinese medicine is a promising alternative for the management of diabetic nephropathy. (April 2015) - Liu, Jing-Yi; Chen, Xiao-Xin; Tang, Sydney Chi-Wai; Lao, Li-Xing; Sze, Stephen Cho-Wing; Lee, Kai-Fai; Zhang, Kalin Yan-Bo
Highlights: DN experimental models for TCM edible plants study are summarized. Anti-DN components from TCM edible plants are discussed. TCM edible plants as diet therapy for DN management is considered. Safety and toxicity of edible plants in DN treatment are explored. Abstract: Diabetic nephropathy (DN) is a serious microvascular complication in diabetes mellitus patients and 30–45% of DN patients progresses to end-stage renal disease, imposing a heavy burden on the society. Unfortunately, the pathogenesis of DN remains unclear, and effective and safe therapies are in great demand. Rather than conventional medicines that concentrate on delaying renal failure by controlling blood sugar and/or ameliorating microalbuminuria, traditional Chinese medicine (TCM) emphasize on the patients' whole inner system and devote to repair the kidney with consideration of overall health. Since many TCM herbs are edible, edible plants from TCM as diet therapy would be a promising alternative for DN management. To date, remarkable progresses have been made on the therapeutic effects of TCM edible plants for DN. In this review, the pathogenesis and experimental models of DN are firstly discussed. Thereafter, the structures of active components from TCM edible plants are summarized followed by discussion of recent research on TCM edible plants as functional food for diet therapy. Additionally, the necessity for safety evaluation of TCM edible plants for DN treatment is addressed.